Ballistic Thermal Transport at Sub‐10 nm Laser‐Induced Hot Spots in GaN Crystal. Issue 2 (17th November 2022) - Huang, Dezhao; Sun, Qiangsheng; Liu, Zeyu; Xu, Shen; Yang, Ronggui; Yue, Yanan
Abstract: Ballistic thermal transport at nanoscale hotspots will greatly reduce the performance of a Gallium nitride (GaN) device when its characteristic length reaches the nanometer scale. In this work, the authors develop a tip‐enhanced Raman thermometry approach to study ballistic thermal transport within the range of 10 nm in GaN, simultaneously achieving laser heating and measuring the local temperature. The Raman results show that the temperature increase from an Au‐coated tip‐focused hotspot up to two times higher (40 K) than that in a bare tip‐focused region (20 K). To further investigate the possible mechanisms behind this temperature difference, the authors perform electromagnetic simulations to generate a highly focused heating field, and observe a highly localized optical penetration, within a range of 10 nm. The phonon mean free path (MFP) of the GaN substrate can thus be determined by comparing the numerical simulation results with the experimentally measured temperature increase which is in good agreement with the average MFP weighted by the mode‐specific thermal conductivity, as calculated from first‐principles simulations. The results demonstrate that the phonon MFP of a material can be rapidly predicted through a combination of experiments and simulations, which can find wide application in the thermal management of GaN‐based electronics. Abstract : In this work, a tip‐enhanced Raman thermometry to study ballistic thermal transport within the range of 10 nm in GaN is developed, simultaneously achieving laser heating and measuring the local temperature. The phonon mean free path (MFP) of the GaN substrate could be determined by comparing the numerical simulation results with the experimentally measured temperature increase.